NOTARY AUTHORITY IN MAKING DEEDS ON LAND ACQUISITION FOR ROAD WIDENING BY THE MINISTRY OF PUBLIC WORKS AND PUBLIC HOUSING - Ahmad Firdan Badawy; Budi Parmono; Rahmatul Hidayati (SOSIOEDUKASI, 2026)
This study aims to analyze the authority of Notaries in drafting deeds of land rights release in land acquisition for road widening conducted by the Ministry of Public Works and Housing (PUPR), as well as to examine the legal consequences of land acquisition carried out without a Notarial deed. The research employs a normative legal research method using a statutory approach and a conceptual approach. Legal materials consist of primary legal sources in the form of relevant laws and regulations, secondary legal materials including legal doctrines and previous studies, and tertiary legal materials as supporting references. The data are analyzed qualitatively through legal reasoning to assess normative consistency and the scope of legal authority in land acquisition practices. The findings indicate that Notaries possess juridical authority to draft authentic deeds related to the release of land rights based on the Law on the Notarial Office; however, such authority is not mandatory within the legal framework governing land acquisition for public purposes. Land acquisition conducted without a Notarial deed remains administratively valid if procedural requirements are fulfilled, yet it may weaken evidentiary strength and increase the risk of future legal disputes.